Transfusion-Associated Hyperkalemic Cardiac Arrest in Neonatal, Infant, and Pediatric Patients - Burke, Morgan; Sinha, Pranava; Luban, Naomi L. C.; Posnack, Nikki Gillum (Frontiers in Pediatrics, 2021)
Abstract: Red blood cell (RBC) transfusions are a life-saving intervention, with nearly 14 million RBC units transfused in the United States each year. However, the safety and efficacy of this procedure can be influenced by variations in the collection, processing, and administration of RBCs. Procedures or manipulations that increase potassium (K+) levels in stored blood products can also predispose patients to hyperkalemia and transfusion-associated hyperkalemic cardiac arrest (TAHCA). In this minireview, we aimed to provide a brief overview of blood storage, the red cell storage lesion, and variables that increase extracellular [K+]. We also summarize cases of transfusion-associated hyperkalemic cardiac arrest (TAHCA) and identify potential mitigation strategies. Hyperkalemia and cardiac arrhythmias can occur in pediatric patients when RBCs are transfused quickly, delivered directly to the heart without time for electrolyte equilibration, or accumulate extracellular K+ due to storage time or irradiation. Advances in blood banking have improved the availability and quality of RBCs, yet, some patient populations are sensitive to transfusion-associated hyperkalemia. Future research studies should further investigate potential mitigation strategies to reduce the risk of TAHCA, which may include using fresh RBCs, reducing storage time after irradiation, transfusing at slower rates, implementing manipulations that wash or remove excess extracellular [K+], and implementing restrictive transfusion strategies.